CULINARY PARK HOTEL Integrasi Kawasan Wisata Pantai Panjang Bengkulu - , GERY DWI SAMUDRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is considered as the biggest archipelago around equator, which is made of 17,508 islands, either big or small, and has a very long coastline reaching 81,000 km total. No wonder Indonesia is rich in beautiful beaches and oceanic resources, along with the diversity of tribes and culture. Tourism development in Indonesia is now growing so fast, so that tourism industry becomes one promising way to gain National Foreign Exchange and the development is expected to be able to improve Indonesian Economic Growth. Bengkulu, a city in Indonesia which itâs attraction point is in the beach, has been trying to represent themselves through the richness of their traditional tourism. Indonesian commodity of the beaches and ocean can be a boomerang in the future if every beach tourism area canât be distinguished from the others, or without particular organizing. Therefore, in order to be able to compete nationally, accomodotion holds a very important role in traditional tourism development. Culinary Park Hotel is a combination between two building tipology, culinary park and hotel which is located on Pantai Panjang tourism area, for the purpose to attain accommodation needs from quantity and quality of design. This combination is expected to be able to accommodate either domestic or national tourist requirements. Using integration of site context and interconnective space as the main concept, hopefully this Culinary Park Hotel can connect every elements in this area so that Pantai Panjang tourism area as a main tourism destination in Bengkulu can be improved. Keywords: Culinary Park Hotel, tourism, area integration, interconnective space